Studies On The Chemistry, Anticholinesterase Activity And Toxicity Of Mitragyna Speciosa (Kratom) Alkaloids - Chear, Nelson Jeng Yeou (2024)
Mitragyna speciosa (korth) havil. Is a medicinal plant native to malaysia, traditionally used to treat pain, diabetes, hypertension, and drug addiction. It is also consumed as a tonic beverage to enhance alertness, attention and working performance among labourers and farmers. Most pharmacological activities documented for m. Speciosa focus on opioid-related activities. Research on the potential therapeutic effects of m. Speciosa on the cholinergic neurotransmission system is still scarce. Only one study has reported the anticholinesterase activity of the methanol extract and mitragynine prepared from thai m. Speciosa. Therefore, this study aims to identify potential cholinesterase inhibitors from m. Speciosa using a bioassay-guided isolation approach. A total of thirteen alkaloids were isolated and characterized from the alkaloid extract using modern chromatographic techniques and spectroscopic methods. The isolated alkaloids were mitragynine (87), speciociliatine (88), speciogynine (89), mitraciliatine (90), paynantheine (91), corynantheidine (101), corynoxine (81), corynoxine b (82), mitrafoline (125), mitragynine oxindole b (117), mitragynine oxindole a (116), 17(z)-speciociliatine (146), and speciociliatine n-oxide (98). Two of these alkaloids, 17(z)-speciociliatine (146) and speciociliatine n-oxide (98), are the new compounds from m. Speciosa. Notably, 17(z)-speciociliatine (146) is the fourth isomer of mitragynine (87), in addition to (88), (89) and (90).